PERUBAHAN SIKAP PEMBACA DALAM MENILAI CHILD GROOMING MELALUI BUKU BROKEN STRINGS - Alifia Nahwa, Faisa; Pandu Mustikasari, Ratih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Broken Strings is an e-book by Aurelie Moeremans that narrates her personal experience as a victim of child grooming and has become one of the most widely accessed and discussed digital works on social media. This study aims to analyze the influence of exposure to the book Broken Strings on readers’ attitude change in assessing child grooming practices, using George Gerbner’s Cultivation Theory as the main theoretical framework. This study employs a quantitative explanatory approach with purposive sampling technique. Data were collected through questionnaires distributed to 100 respondents and analyzed using simple linear regression with SPSS Statistics. The independent variable (X) is exposure to the book Broken Strings, measured through frequency, duration, and reading attention, while the dependent variable (Y) is readers’ attitude change measured through cognitive, affective, and conative aspects. The results indicate that exposure to the book Broken Strings has a positive and significant influence on readers’ attitude change in assessing child grooming, with a t-value of 7.724 > t-table of 1.984 and significance value of 0.000 < 0.05, thus H₁ is accepted. The regression equation obtained is Y = 1.348 + 0.966X with a Beta value of 0.615. The coefficient of determination (R²) of 0.378 indicates that 37.8% of the variation in attitude change is explained by the exposure to the book Broken Strings, while the remaining 62.2% is influenced by other factors outside the research model.